Drawing on principles of Dance Movement Therapy practice in a South African water research context - Copteros, Athina (Rhodes University, Faculty of Humanities, Department of Fine Art, 2017)
Research that draws on principles of Dance Movement Therapy in a South African water research context has not been done before. In order to initiate this exploration, culturally relevant themes from professional training in the United Kingdom were identified that could be developed in the context of trans-disciplinary water resource management research in South Africa. Hermeneutic phenomenology provided the methodological framing for this study. Interpretative Phenomenological Analysis was used to discover culturally relevant themes based on the recorded perceptions of the phenomenon of the training while it was taking place. The themes of: 'awareness of power and difference'; 'therapeutic adaptability'; 'safety and ownership' and 'connecting with the environment' emerged as overriding themes. Influences from Artistic Inquiry informed the inclusion of a creative embodied response to the themes that emerged. These themes then informed the application of some relevant principles of Dance Movement Therapy practice within a trans-disciplinary complex social-ecological systems researcher group. Eight members of the group participated in the study. They represented a range of academic research roles, genders and backgrounds. They reflected on their experience of an introductory session and five Dance Movement Therapy based sessions in semi-structured interviews. Using Interpretative Phenomenological Analysis, four themes were identified that capture the quality of the participants' shared experience of the phenomenon: 'community engagement'; 'embodiment'; 'individual and group identity' and 'integration'. Based on the integration of themes, it is concluded that principles of Dance Movement Therapy have a contribution to make. Core tenets of Dance Movement Therapy such as: inclusion of body and emotion; healing from trauma through embodiment; group processes held with safety and acceptance; and a deep level of connection to self, each other and the wider ecology, address some of the basic challenges of trans-disciplinary complex social ecological systems research practice. Through researchers experiencing principles of DMT practice for themselves and reflecting on their experience, it is possible that their embodied knowledge and reflections will influence and inform their engagement with communities in the future.
Keywords: Water-supply -- Management -- South Africa; Dance therapy; Movement therapy; Dance therapy -- South Africa; Movement therapy -- South Africa; Interdisciplinary research; Interdisciplinary approach to knowledge; Environmental education; Environmental education -- South Africa